Characterization and Modelling of the Deformation and Failure of Engineering Metallic Materials - Hui Wang; Lihong Su; Ebad Bagherpour; Qiang Xing (Crystals, 2025)
Metallic materials are at the heart of modern industry and infrastructure, valued for their outstanding strength, ductility, and other excellent mechanical properties [...]